2018
DOI: 10.1177/1467358418798141
|View full text |Cite
|
Sign up to set email alerts
|

An application of the Fama–French three-factor model to lodging REITs: A 20-year analysis

Abstract: This study applied the Fama–French three-factor model to model the returns of 33 US publicly traded lodging real estate investment trusts over a 20-year period. Results indicated that lodging real estate investment trusts that were significantly correlated with all the three factors had the greatest number of years in the market and the highest mean market capitalization, while those that were not significantly correlated with any of the three factors existed in the market for shorter periods and had the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…𝑅 𝑖𝑡 − 𝑅 𝑓𝑡 = 𝛼 𝑖 + 𝛽 𝑖 (𝑅 𝑚𝑡 − 𝑅 𝑓𝑡 ) + 𝑠 𝑖 𝑆𝑀𝐵 𝑡 + ℎ 𝑖 𝐻𝑀𝐿 𝑡 + 𝑟 𝑖 𝑅𝑀𝑊 𝑡 + 𝑐 𝑖 𝐶𝑀𝐴 𝑡 + 𝜀 𝑖𝑡 (2) In this formula, RMW is the difference between the return of high-profit stock portfolio and low-profit stock portfolio, while CMA is the difference between the return of high reinvestment proportion company's stock portfolio and low reinvestment proportion company's stock portfolio. These two items describe profit level risk and investment level risk respectively.…”
Section: Fama-french Five-factor Model Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…𝑅 𝑖𝑡 − 𝑅 𝑓𝑡 = 𝛼 𝑖 + 𝛽 𝑖 (𝑅 𝑚𝑡 − 𝑅 𝑓𝑡 ) + 𝑠 𝑖 𝑆𝑀𝐵 𝑡 + ℎ 𝑖 𝐻𝑀𝐿 𝑡 + 𝑟 𝑖 𝑅𝑀𝑊 𝑡 + 𝑐 𝑖 𝐶𝑀𝐴 𝑡 + 𝜀 𝑖𝑡 (2) In this formula, RMW is the difference between the return of high-profit stock portfolio and low-profit stock portfolio, while CMA is the difference between the return of high reinvestment proportion company's stock portfolio and low reinvestment proportion company's stock portfolio. These two items describe profit level risk and investment level risk respectively.…”
Section: Fama-french Five-factor Model Theorymentioning
confidence: 99%
“…In particular, the epidemic is undoubtedly a severe challenge for the biopharmaceutical industry. [2]. Samir et al used the data of the Moroccan Stock Market (MSM) from 2005 to 2009 to test the applicability of Fama-French three-factor model.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that risk premiums on equity REITs were significantly related to the three stock-market factors (explaining returns to equity REITs' shareholders), whereas mortgage REITs were related to the three stockmarket factors and the two bond-market factors in relation to returns, although they could not explain returns to mortgage REITs' shareholders under the research period. Jackson (2018) applied the FF3 model to examine the returns of 33 US publicly trade lodging REITs over a 20-year period. The empirical results indicated that most object lodging REITs were significantly correlated with all three factors (market, size and value) and they had a positive influence on the selected US REITs' returns.…”
Section: Number Of Reits Creadedmentioning
confidence: 99%
“…If the size factor (SMB) permanently increases by 1 unit, the equilibrium value of S-REITs' required rate of returns will increase by 7.584 units. The positive value suggests that S-REITs are likely to be exposed to the "size risk", to which small companies tend to be sensitive (Fama and Frence, 1992;Jackson, 2018); in other word, portfolios consisting of small companies could be expected to bring higher returns with a higher risk in the long run potentially increasing the exposure to the risk of small REITs. Finally, the long-run multiplier effect of the value factor (HML) on the expected rate of returns (RÀR f ) is À12.265 units; this negative number suggests that the S-REITs' excess returns are also negatively affected by HML in the analysis period suggesting that the excess of returns in the short term will diminish convergint to the mean in the long term.…”
Section: Empirical Analysismentioning
confidence: 99%
“…The performance of lodging real estate investment trusts is highly tied to elements such as market, book-to-value, and size. [7] Another recent study investigates and demonstrates that Fama-French model is applicable to Islamic trust funds throughout a market crash. [8] Yu's study references Fama-French Model's factors, exploring the significance of investor sentiment in the United States stock market.…”
Section: Introductionmentioning
confidence: 99%